Psycho-Social Issues of Middle Aged Working Women in Cochin City Based on Stress: Exploring the Impact of Stress on Middle Aged Working Women in Cochin City (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women all around the world hold a major role in the economic and social development of its nation. The multiple roles and overlapping responsibilities she has, to support her family financially, emotionally and physically takes a toll on her physical, emotional and mental health. Stress levels are higher in middle aged working women as there is a shift from adulthood to old age and as a result the physical contributions by the body in response to the mental stress increases with age and professional variance. The stress levels of the same age group differ according to their professional competencies. Stress is also considered as a part of the package with City life. The significance of this study is to identify the psycho-social issues related to stress in middle-aged working women at the city level, the underlying causes and levels that stress affects the human body and to identify the salient features of stress and hence determine the respondents’ perception and response to the different levels of it. Based on this regard, identify its implication and help women face stress with a positive attitude, and use different remedial measures and interventions to enhance their life and well-being.